Regulating WOx coordination environment improves proton transfer for catalytic amine regeneration in CO2 capture - Zanbu Geng; Yang Yang; Wenqing Xu; Yixi Wang; Yiren Li; Chaoqun Li; Juan Liu; Tingyu Zhu (Green Energy & Environment)
Catalyst-aided regeneration is a promising method for reducing the high regeneration energy consumption of amine-based CO2 capture technologies. However, the intrinsic relationship between the properties of the acidic sites and their catalytic activity is controversial. In this study, a series of W-based catalysts supported by ZrTiOx were synthesised, and the effects of the intensity, distribution, and type of acid sites were systematically investigated by quantitatively regulating the acidic site properties. The results indicate stronger acidic sites play a more important role in the catalytic reaction. Moreover, the catalysts showed excellent performance only if the Brønsted acid sites (BASs) and Lewis acid sites (LASs) coexisted. During the catalytic reaction, the BASs facilitated deprotonation, and the LASs promoted the decomposition of carbamates. The ratio of BASs to LASs (B/L) was a critical factor for catalytic activity, wherein optimal performance was achieved when the B/L ratio was close to 1. The 10% HPW/ZrTiOx composite performed better than WO3/ZrTiOx and HSiW/ZrTiOx because it had a stronger acid intensity and a suitable B/L ratio. As a result, the relative heat duty was reduced by 47% compared to 30% aqueous MEA, and the maximum CO2 desorption rate was increased by 83%. The Bader charge indicated that the W atoms of HPW/ZrTiOx lost more electrons (0.18) than those of WO3/ZrTiOx, which can weaken the O–H bond energy. Consequently, the calculated deprotonation energy is as low as 257 kJ mol−1 for HPW/ZrTiOx.